2011
DOI: 10.1007/s11251-011-9191-4
|View full text |Cite
|
Sign up to set email alerts
|

Learning study: helping teachers to use theory, develop professionally, and produce new knowledge to be shared

Abstract: The lesson study approach is a systematic process for producing professional knowledge about teaching by teachers, and has spread rapidly and extensively in the United States. The learning study approach is essentially a kind of lesson study with an explicit learning theory-the variation theory of learning. In this paper, we argue that having an explicit learning theory adds value to lesson study, as the variation theory of learning serves as a source of guiding principles for the teachers when they engage in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 22 publications
3
103
0
19
Order By: Relevance
“…One overall purpose with the learning study approach is "to generate data that enable us to establish the relationship between teaching and learning" (Pang & Ling, 2012), i.e. "to help teachers to help students learn the object of learning" (Ling & Marton, 2012 p. 8).…”
Section: Learning Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One overall purpose with the learning study approach is "to generate data that enable us to establish the relationship between teaching and learning" (Pang & Ling, 2012), i.e. "to help teachers to help students learn the object of learning" (Ling & Marton, 2012 p. 8).…”
Section: Learning Studiesmentioning
confidence: 99%
“…The chosen objects of learning was also a result of the teachers' earlier experiences of pupils' difficulties in building solid constructions in general, and with 4Dframe in particular. Pang and Ling (2012) emphasise two important elements in the learning study approach. The first is the distinct focus on the object of learning, and the second is variation theory as a tool in the learning study process.…”
Section: Technology Education and Hands-onmentioning
confidence: 99%
“…Collaboratively, teachers develop a lesson plan, teach and observe the lesson, collect data on student learning, and use their observations to refine their lesson (Marton and Pang, 2006;Pang, 2006;Stepanek et al, 2007). An effective Learning Study improves students learning by promoting high quality teachers" professional development (Pang & Ling, 2012;Runesson, 2015), among others.…”
Section: Theoretical Contextmentioning
confidence: 99%
“…These projects' results have indicated that such models are useful for: 1) developing learning about and understanding of a concept or phenomenon (Lo, Pakey, & Pang, 2006;Wernberg, 2009); 2) reducing the gap between high and low achievers (Lo, 2012;Lo & Marton, 2012); and 3) improving teaching practice and teachers' professional development (Cheng & Lo, 2013;Pang, 2006;Pang & Lo, 2011) and student teachers' (Brante, Holmqvist Olander, Holmquist, & Palla, 2014;Davies & Dunnill, 2008) knowledge of teaching and learning. Knowledge of how the LS model can be tailored to ECE practice is under development.…”
Section: Previous Use Of Ls In Ece Practicementioning
confidence: 99%